The Removal of Cr(VI) from Aqueous Solution by Activated Carbon Prepared from Apricot, Peach Stone and Almond Shell Mixture in a Fixed-Bed Column - Yuksel, Seyma; Orhan, Ramazan (Springer Heidelberg, 2019)
The purpose of the study is to remove Cr(VI) from aqueous solutions in a fixed-bed column under different operating conditions [pH, influent Cr(VI) concentration, flow rate, bed height and temperature]. To this end, activated carbon prepared of apricot, peach stones and almond shell mixture was used. Adsorption capacity increased with the increase in bed height and influent Cr(VI) concentration, while it decreased with the increase in flow rate, pH and temperature. The adsorption capacity was found as 6.67mg/g under optimum conditions. Adams-Bohart, Thomas and Yoon-Nelson models were applied to experimental data to find the kinetic parameters. It was determined that the appropriate model describing the adsorption mechanism was Thomas. As a result, the new activated carbon used in this study indicates its applicability in the removal of Cr(VI) ions in industrial wastewater.
Keywords: Cr(VI); Adsorption; Activated carbon; Fixed-bed; Triple mixture